Impact of COVID-19 on athletes and coaches, and their values in Japan: Repercussions of postponing the Tokyo 2020 Olympic and Paralympic Games - Taku, K.; Arai, H. (Journal of Loss and Trauma: International Perspectives on Stress & Coping, 2020)
On 24 March 2020, an announcement was made that the Tokyo 2020 Olympic and Paralympic games would be postponed until 2021 due to the coronavirus pandemic. Athletes and their coaches have experienced a wide spectrum of emotional and cognitive reactions such as disappointment, frustration, confusion, and relief, to name a few. The current article aimed to summarize the athletes` and coaches` reactions related to the repercussions triggered by the postponement of the Tokyo 2020 Olympic and Paralympic Games in Japan, and discuss how the values of sports and athletes have or are likely to be changed.